A study on identification of borehole ballooning in the formation with narrow safe density window. Issue 1 (2nd January 2019) - Li, Cheng; Guan, Zhichuan; Zhang, Bo; Sheng, Yanan; Wang, Qing; Wang, Xiaohui; Han, Chao
ABSTRACT: Borehole ballooning is a special phenomenon observed during drilling operations in the formation with a narrow safe density window. This phenomenon is easy to be confused with well kick. This study takes a comparison between borehole ballooning and well kick and finds that the essential distinction is whether the influx of formation fluid happens. TTake the event of 'overflow at well head' as the initial event and draw an event tree with five process events to analyze the reason of "overflow at well head." Finally, draw a flowchart to identifyborehole ballooning under the situation of narrow-formation safe density window.